A conversation on power and republicanism: an exchange between Mark Haugaard and Philip Pettit. Issue 1 (2nd January 2017) - Haugaard, Mark; Pettit, Philip
ABSTRACT: In this exchange Haugaard and Pettit begin by discussing power and agency. They agree that while many inequalities are linked to deliberate agency, a significant number of inequalities comprise structural effects that are the unintended effect of social action. These are of normative concern: to prevent arbitrary domination and create a society in which everyone can pass the eyeball test. Some of these structures are naturalized, or reified, which often makes them appear less contestable. This includes private property, which is presented as part of the natural order of things, thereby often naturalizing domination. From these beginnings, the authors discuss the nature of the eye-ball and tough-luck tests, including: how they apply to culture, parent–child power, gender, and economic inequalities.